A Compositional Approach to Structuring and Refinement of Typed Graph Grammars - Corradini, Andrea; Heckel, Reiko (Proceedings of the Joint COMPUGRAPH/SEMAGRAPH Workshop on Graph Rewriting and Computation (SEGRAGRA 1995), Volterra (Italy))
Based on a categorical semantics that has been developed for typed graph grammars we uses colimits (pushouts) to model composition and (reverse) graph grammar morphisms to describe refinements of typed graph grammars. Composition of graph grammars w.r.t. common subgrammars is shown to be compatible with the semantics, i.e. the semantics of the composed grammar is obtained as the composition of the semantics of the component grammars. Moreover, the structure of a composed grammar is preserved during a refinement step in the sense that compatible refinements of the components induce a refinement of the composition. The concepts and results are illustrated by an example.

GRAPHIT: Graphical Support and Integration of Formal and Semiformal Methods for Software Specification and Development - Bardohl, Bernhard; Bardohl, Roswitha; Castro, Paulo; Ehrig, Hartmut; Heckel, Reiko; Ribeiro, Leila; Nunes, Daltro; Martini, Alfio (Proceedings of the 3rd German-Brazilian Workshop on Information Technology (1995), Berlin (Germany))
The overall aim of this paper is a proposal how to bridge the gap between formal specification techniques developed in research projects and semi--formal or informal specifications used in industrial practice. The main idea to overcome these problems is to develop graphical support for formal methods in order to increase acceptance by practitioners and to provide means for integration of formal and semi--formal methods. More specifically suitable concepts will be developed to combine algebraic specifications, Petri Nets, and Graph Grammars with each other and with distinguished graphical components to be used by industrial partners.

Encapsulated Hierarchical Graphs, Graph Types, and Meta Types - Engels, Gregor; Schürr, Andy (Proceedings of the Joint COMPUGRAPH/SEMAGRAPH Workshop on Graph Rewriting and Computation (SEGRAGRA 1995), Volterra (Italy))
Currently existing graph grammar-based specification languages have serious problems with supporting any kind of “specification-in-the-large” activities. More precisely, they have deficiencies with respect to modeling hierarchical data structures or specifying meta activities like manipulation of graph schemata. Furthermore, already proposed graph grammar module concepts are still too abstract to be useful in practice. Our contribution addresses these problems by introducing a new hierarchical graph data model with an infinite number of schema, meta-schema, etc. layers. It forms the base for a forthcoming concrete modular graph grammar specification language where in addition information hiding aspects like explicit export and import interfaces are expressible.

Ensuring Consistency of Conditional Graph Grammars - A constructive Approach - Heckel, Reiko; Wagner, Annika (Proceedings of the Joint COMPUGRAPH/SEMAGRAPH Workshop on Graph Rewriting and Computation (SEGRAGRA 1995), Volterra (Italy))

Existenzgründung - Kremer, H.-Hugo (Meisterprüfung - Lernen für die Praxis - Unternehmensführung 1)

Symmetry Breaking Bifurcations of Chaotic Attractors - Aston, Philip J.; Dellnitz, Michael (International Journal of Bifurcation and Chaos)
In an array of coupled oscillators, synchronous chaos may occur in the sense that all the oscillators behave identically although the corresponding motion is chaotic. When a parameter is varied this fully symmetric dynamical state can lose its stability, and the main purpose of this paper is to investigate which type of dynamical behavior is expected to be observed once the loss of stability has occurred. The essential tool is a classification of Lyapunov exponents based on the symmetry of the underlying problem. This classification is crucial in the derivation of the analytical results but it also allows an efficient computation of the dominant Lyapunov exponent associated with each symmetry type. We show how these dominant exponents determine the stability of invariant sets possessing various instantaneous symmetries, and this leads to the idea of symmetry breaking bifurcations of chaotic attractors. Finally, the results and ideas are illustrated for several systems of coupled oscillators.

Admissible symmetry increasing bifurcations - Dellnitz, M; Heinrich, C (Nonlinearity)

A note on the shadowing lemma and symmetric periodic points - Dellnitz, M; Melbourne, I (Nonlinearity)

Cycling Chaos - Dellnitz, Michael; Field, Michael; Golubitsky, Martin; Ma, Jun; Hohmann, Andreas (International Journal of Bifurcation and Chaos)

Spirals in Scalar Reaction–Diffusion Equations - Dellnitz, Michael; Golubitsky, Martin; Hohmann, Andreas; Stewart, Ian (International Journal of Bifurcation and Chaos)
Spiral patterns have been observed experimentally, numerically, and theoretically in a variety of systems. It is often believed that these spiral wave patterns can occur only in systems of reaction–diffusion equations. We show, both theoretically (using Hopf bifurcation techniques) and numerically (using both direct simulation and continuation of rotating waves) that spiral wave patterns can appear in a single reaction–diffusion equation [ in u(x, t)] on a disk, if one assumes "spiral" boundary conditions (u r = mu θ ). Spiral boundary conditions are motivated by assuming that a solution is infinitesimally an Archimedian spiral near the boundary. It follows from a bifurcation analysis that for this form of spirals there are no singularities in the spiral pattern (technically there is no spiral tip) and that at bifurcation there is a steep gradient between the "red" and "blue" arms of the spiral.

Transforming comparison model lower bounds to the parallel-random-access-machine - Breslauer, Dany; Czumaj, Artur; Dubhashi, Devdatt P.; Meyer auf der Heide, Friedhelm (Information Processing Letters)

The constrained Liapunov-Schmidt procedure and periodic orbits - Golubitsky, Martin; Marsden, Jerrold; Stewart, Ian; Dellnitz, Michael (Normal Forms and Homoclinic Chaos)

A packet routing protocol for arbitrary networks - Meyer auf der Heide, Friedhelm; Vöcking, Berthold (STACS 95)

Shared memory simulations with triple-logarithmic delay - Czumaj, Artur; Meyer auf der Heide, Friedhelm; Stemann, Volker (Lecture Notes in Computer Science)

Optimal trade-offs between size and slowdown for universal parallel networks - Meyer auf der Heide, Friedhelm; Storch, Martin; Wanka, Rolf (Proceedings of the seventh annual ACM symposium on Parallel algorithms and architectures - SPAA '95)

Improved optimal shared memory simulations, and the power of reconfiguration - Czumaj, Artur; Meyer auf der Heide, Friedhelm; Stemann, Volker (Proceedings Third Israel Symposium on the Theory of Computing and Systems)

Hot-potato routing on multi-dimensional tori - Meyer auf der Heide, Friedhelm; Westermann, Matthias (Graph-Theoretic Concepts in Computer Science)

Truly efficient parallel algorithms: c-optimal multisearch for an extension of the BSP model - Bäumker, Armin; Dittrich, Wolfgang; Meyer auf der Heide, Friedhelm (Lecture Notes in Computer Science)

Exploiting Parallelism in Constraint Satisfaction for Qualitative Simulation - Platzner, Marco; Rinner, Bernhard; Weiss, Reinhold (J.UCS Journal of Universal Computer Science)

Application of Clustering Techniques to Mixture Density Modelling for Continuous-Speech Recognition - Dugast, Christian; Beyerlein, Peter; Haeb-Umbach, Reinhold (ICASSP, Detroit)
Clustering techniques have been integrated at different levels into the training procedure of a continuous-density hidden Markov model (HMM) speech recognizer. These clustering techniques can be used in two ways. First acoustically similar states are tied together. It will help to reduce the number of parameters but also allow to train otherwise rarely seen states together with more robust ones (state-tying). Secondly densities are clustered across states, this reduces the number of densities while at the same time keeping the best performances of our recognizer (density-clustering). We have applied these techniques both to word-based small-vocabulary and phoneme-based large-vocabulary recognition tasks. On the WSJ task, we could achieve a reduction of the word error rate by 7%. On the TI/NIST-connected digit task, the number of parameters was reduced by a factor 2-3 while keeping the same string error rate.